BIOINDICATION AS AN ECOLOGICAL MONITORING METHOD IN REZEKNE CITY - Reinikova, Larisa; Tretjakova, Rasma (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The article discusses methods of air bioindecation using lichens and the condition of needles in conifers. Monitoring methods and air quality are described. Methods of methods for analyzing air by studying lichen on trees are described, three methods are considered and used in studies, and the method for assessing air quality by the state of needles of coniferous trees is also used in studies. As a result of the study, the air quality in the city of Rezekne was assessed. According to the results of the study, the air quality in most of the city of Rezenke is low pollution.